Minor Representations: From Anne Frank to Bana Alabed – The Radically Performative Literacies of a Viral Child. (1st May 2020) - Trezise, Bryoni
Abstract: In this article, I construct a comparative analysis of two forms of child-authored life-narrative: the famous Diary of a Young Girl written by Anne Frank and the contemporary Twitter stream authored by the Syrian child-writer Bana Alabed. My interest in these two textual practices is focused on how they each formulate notions and experiences of temporality that are central to how conceptions of the modern, innocent child and its most recent counterpart – a figure whom I term the viral child – function. Across this analysis, I observe how the textual utterances performed by each child-author make specific claims about the autobiographical 'I' as it enacts a literary relationship to the temporality of its ongoing construction. I argue that the radical shift in relations between the child-figure and the future cast by Alabed's tweets positions the viral child as not only a voice, but also a medium, of the cultural present.